A Defensoria Pública rumo ao novo paradigma de acesso à justiça ambiental - Dorilêo, Márcio Frederico de Oliveira (2012)
The study aims to demonstrate the construction of the new paradigm of environmental protection, represented by the performance of the Public Defense, an institution dedicated to promote the human rights. The human rights, its evolution and characterization as well as protection systems has been analyzed, in order to identify and establish the interconnection between human rights and the right to an ecologically balanced environment, present in the Federal Constitution. The international systems of protection of the environment, as well as legal protection in Brazilian law were also studied. Moreover, an analysis was made regarding the right to environmental information, public participation and access to environmental justice, that are essential issues to the effective protection of the environment, which can be secured through the Public Defense. Legal texts, doctrines and decisions of the Brazilian courts were also studied, which serve as subsidies in the statement of the institutional functions of the Public Defense, while a duty of the state in its role in the environmental sphere. There was also the importance of ensuring the full and free legal assistance to people in need, such as the affirmative action policy and human rights tool for quick distribution, equal and effective justice, demonstrating changes in the legislation, which allows to check the expansion of mechanisms protection of the environment, provided by the Public Defense, with various forms of protection.